Проклятие тангеры: мистический роман / Юлия Аксенова - Аксенова Юлия Александровна (Бессонница, 2010)
Экземпляры: Ф. 13 (20190626) / Инвентарный номер: 42880 / Цена: 54.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 42 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6